Stigma theory and religion in the workplace - Thomson, Stanley Bruce (My University, 2010)
The application stigma theory provides significant insights into the strategies used to manage one's own religious beliefs and the beliefs of others in the workplace. Avoidance is the most common method used by participants and religious belief guided participants in their choice of jobs, the organization and their decisions to leave.
Presented on August 6-10, 2010 at the Academy of Management Annual Meeting, held in Montreal, Quebec.
Keywords: work environment; industrial psychology; religious beliefs